Peningkatan Kemampuan Berbahasa Inggris Bagi Siswa SMP - Nur Budi Nugraha; Julanos Julanos; Jhon Suarlin (Politeknik Negeri Cilacap, 2020)
One of the main objectives of studying English is to increase ability in English conversation. However, English conversation skills are still considered as one of the skills that are difficult for students to do. Many students face some difficulties when they want to communicate in English, even though they have studied English for years. Some of the difficulties students often face and complain about are the first, they are not able to communicate in English, because they do not master English vocabulary. Secondly, they are afraid and lacking confidence in the ability to speak English vocabulary, and thirdly, there is no attractive media and learning methods to involve students communicating in English. Therefore, effective and efficient solutions are needed to increase students' interest in understanding English subjects by providing interesting teaching media and effective learning methods. One of the interesting teaching media is the use of ICT (Information and Communication Technology) into it, one of which is video animation. Effective and efficient media and methods can help students engage in learning English and at the same time be motivated to communicate in English. The target of the implementation of this community service activity is Class 7 students of Bazma Brilliant Middle School. This activity provides knowledge about the media and methods of learning English conversation in the form of tips and strategies to increase students' interest in learning and communicating in English.